Conceptual Design of an Anti-collision System for Light Rail Vehicles - Mariusz WAŻNY; Krzysztof FALKOWSKI; Mirosław WRÓBLEWSKI; Konrad WOJTOWICZ; Adam MARUT (Problemy Mechatroniki, 2021)
This paper presents the concepts for an anti-collision system intended for trams. The purpose of the anti-collision system is to develop and provide information to support the driver’s decision to initiate the braking of a tram. The anti-collision system is based on the processing of data from multiple sources (obstacle detection, image processing, and visual light communication system) and an expert system. The information about the road situation is visually presented on HUD (Head-up Display) of the driver.